Three-dimensional ZIF-67 attached lamellar Ti3AlC2 combined with ZnAl-LDH as cathode catalyst for enhancing oxygen reduction reaction of microbial fuel cells. (29th April 2022) - Chen, Junfeng; Yang, Jiaqi; Wu, Yiqun; Zhao, Yongyue; Wang, Xuemei; Wang, Jingyu; Yang, Daoxin; Wang, Yongle; Wei, Qingying; Wang, Renjun; Yang, Yuewei; Liu, Yanyan
Abstract: In this study, a simple hydrothermal method was used to prepare the cathode catalyst of microbial fuel cells (MFCs). The three-dimensional structure of ZIF-67 attached to the lamellar Ti3 AlC2 /ZnAl-layered double hydroxide (LDH) was observed. (010), (012), (015) were the obvious peaks of the composite ZIF-67@Ti3 AlC2 /ZnAl-LDH. Ti, N, C, Al, O, F were relatively uniformly distributed on the surface of the composite material. The maximum voltage of ZIF-67@Ti3 AlC2 /ZnAl-LDH-MFC was 576 mV and the stabilization time was 8 d. The maximum power density of ZIF-67@Ti3 AlC2 /ZnAl-LDH-MFC was 587 mW/m 2, which was 1.32 times of Ti3 AlC2 /ZnAl-LDH-MFC (446 mW/m 2 ) and 2.69 times of Ti3 AlC2 -MFC (218 mW/m 2 ). Ti3 AlC2 with large interlayer spacing and high specific surface area were perfectly composited with multi-layer nanosheets of ZnAl-LDH, and ZIF-67 attached to the surface enhanced the reaction center and activity of the composite material, which promoted oxygen reduction reaction and improved MFC performances. Graphical abstract: Image 1 Highlights: ZIF-67@Ti3 AlC2 /ZnAl-LDH was successfully prepared by water bath heating method. ZIF-67@Ti3 AlC2 /ZnAl-LDH was multilayered, active centers and catalytic. Maximum power density of ZIF-67@Ti3 AlC2 /ZnAl-LDH-MFC was 587 mW/m 2 . Lamellar overlapping Ti3 AlC2 /ZnAl-LDH and ZIF-67 promoted performances.